What is the solution to this equation?? Please explain steps

Let f(x)=x^2+7 and g(x)= (x-3)/x
Find (f@g)(-3)

1 Answer
May 28, 2018

11

Explanation:

The @ notation is to indicate compound functions. Specifically, f@g(x) = f(g(x)). To evaluate this, you sub in the value of g(x) into f(x).

f@g(-3) = f(g(-3)) = f((-3-3)/-3) = f(2) = 2^2 + 7 = 11

Another method to do this is to evaluate the compound function directly, and substitute in the value of -3.

f@g(x) = f(g(x)) = f((x-3)/x) = ((x-3)/x)^2 + 7.

f@g(-3) = ((-3-3)/-3)^2 + 7 = 11